Experimental analysis of performance degradation of 3-cell PEMFC stack under dynamic load cycle. (28th April 2020) - Han, Jaesu; Han, Jaeyoung; Yu, Sangseok
Abstract: A vehicular fuel cell is dynamically operated at the demand of the driver, so that the durability of the fuel cell quickly deteriorates. This study analyzes the durability of a 3-cell short stack under normal vehicle operation. An acceleration test is scheduled with operation temperatures of 55 °C and 70 °C at 50% relative humidity for 300 h. The dynamic load cycle (DLC) conditions are a repetition of the New European Driving Cycle (NEDC), which can allow a short stack to run on the vehicle operating load. At 100-hour intervals, recovery procedures are conducted to understand the order of performance retrieval. Significant stack degradation is observed at 75 °C operation for 300 h. Results show that the recovery protocol can return the performance of the fuel cell at a low and a middle current density regime, but it is hard to recover the performance at a very high current density regime. Performance recovery is very effective for lower temperature operation (55 °C), but the recovery procedures only returned about 4% of the performance at 300 h and 75 °C. Highlights: The 3-cells short stack is used to analyze the durability of a fuel cell stack. An acceleration test was scheduled at 50% relative humidity for 300 h. The dynamic load cycle were applied to run on the vehicle operating load. Significant performance degradation is observed for 300 h of operation. Results showed that the performance recovery was very effective at lower temperature.